2017
DOI: 10.1007/s11255-017-1729-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between uremic toxin-anthranilic acid and fibrinolytic system activity in predialysis patients at different stages of chronic kidney disease

Abstract: PurposeChronic kidney disease (CKD) is an estimated risk factor for increased mortality and morbidity due to fibrinolytic system disturbances. Progressive loss of renal function leads to retention of uremic toxins. Anthranilic acid (AA) is a tryptophan-derived uremic toxin with multidirectional properties that can affect the hemostatic system. The goal of this study was to examine the association between AA and the parameters of fibrinolysis at different stages of CKD.MethodsPatients with CKD were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Kynurenine is positively associated with vWF [ 34 ] and with prothrombin fragments F(1+2), reflecting hypercoagulability in CKD patients [ 35 ]. AA is also significantly associated with TF and prothrombin fragments F(1+2) [ 35 ], and negatively correlated with the fibrinolytic system uPA/uPAR in severe-to-end-stage CKD [ 36 ]. QA is positively associated with vWF [ 34 ], TF, and prothrombin fragments F(1+2) [ 35 ].…”
Section: Thrombotic Mechanisms Induced By Tryptophan-derived Uremimentioning
confidence: 99%
“…Kynurenine is positively associated with vWF [ 34 ] and with prothrombin fragments F(1+2), reflecting hypercoagulability in CKD patients [ 35 ]. AA is also significantly associated with TF and prothrombin fragments F(1+2) [ 35 ], and negatively correlated with the fibrinolytic system uPA/uPAR in severe-to-end-stage CKD [ 36 ]. QA is positively associated with vWF [ 34 ], TF, and prothrombin fragments F(1+2) [ 35 ].…”
Section: Thrombotic Mechanisms Induced By Tryptophan-derived Uremimentioning
confidence: 99%
“…A total of five studies [2326, 28] compared suPAR concentrations between CKD patients and normal controls. Of the five studies, four were from Poland and the other [26] was from the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrinolysis is enhanced in CKD, as demonstrated by higher levels of tissue plasminogen activator (t-PA) and plasminogen activator inhibitor 1 (PAI-1) in this setting compared to healthy controls [ 58 , 73 ]. Likewise, there are also higher serum levels of D-dimer, a product of fibrin degradation, in CKD patients [ 55 ].…”
Section: Endothelial Dysfunction In Ckdmentioning
confidence: 99%
“…In vivo, Karbowska et al [ 72 ] found increased levels of PAI-1, but not of D-dimer, in rats treated with IS compared to control group. Therefore, both coagulation and fibrinolysis systems are altered in CKD [ 58 , 73 , 74 ].…”
Section: Endothelial Dysfunction In Ckdmentioning
confidence: 99%